Effectiveness of Video-assisted Teaching on Knowledge Regarding Organ Donation among Adolescents in Selected Junior College - Palde, Poonam; Deshpande, Rupali; Shinde, Ekta; Gurav, Arundhati; D’souza, Florance (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: This study aims to assess the effectiveness of video-assisted teaching on knowledge regarding organ donation among adolescents in selected junior college and to differentiate in pre-test and post-test knowledge level of adolescents. Methodology: Quantitative research approach with quasi-experimental one-group pretest-posttest design was used for the study. A total of 100 adolescents were selected as sample for study using purposive sampling technique. That 100 samples equally divided into five groups each group containing 20 samples. Data were collected using structured knowledge questionnaires. Each group was covered on a separate day. Video-assisted teaching was also administered on the same day following the pre-test in each group on separate day according to distribution. After 7 days, post-test was conducted to assess the gain in knowledge using the same structured knowledge questionnaire. Results: Adolescent’s post-test knowledge mean score 26.98 was higher than their pre-test knowledge mean score 16.87. The mean post-test knowledge score (26.98) was apparently higher than the pre-test knowledge score (16.87) interpret that the video-assisted teaching was effective in increasing the knowledge of adolescents regarding organ donation. The calculated t value for knowledge (17.00) is more than the table value (1.66) at 99° of freedom for 0.05 level of significance. Thus, null hypothesis H0 is rejected and research hypothesis H1 is accepted which conclude that video-assisted teaching was effective in improving the knowledge of the adolescents regarding organ donation. Conclusion: There was a significant difference in the pre-test and post-test knowledge score of adolescents, which indicated that video-assisted teaching on organ donation is effective in improving knowledge of adolescents.